Pengaruh Cahaya dan Penyiraman Terhadap Kualitas Pembibitan Tanaman Bayur (Pterospermum javanicum) di UPTD BSPTH Dinas Kehutanan Provinsi Sumatera Barat - Lala Deswita; Moralita Chatri; Mika Lestaria (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2026)
The bayur tree (Pterospermum javanicum) is a forestry species that is relatively easy to cultivate and adapts well to local climatic conditions, making it an ideal choice for large-scale nursery programs. Land rehabilitation efforts require a supply of high-quality seedlings, as these seedlings are better able to adapt and thrive in sites that match the characteristics of their tree species, thereby improving the success of planting efforts in rehabilitation projects This study aims to determine the effects of lighting and watering on the quality of Bayur (Pterospermum javanivum) seedlings. The study was conducted from January 5 to February 18, 2026, as part of an internship at the UPTD Forest Tree Certification and Seed Production Center, Department of Forestry, West Sumatra Province. The study employed direct observation and field practice methods, presenting descriptive data in the field of forest tree seedling propagation. The results indicate that plants with optimal lighting and regular watering exhibit high-quality seedling growth when proper procedures are followed. This activity provided students with practical experience in applying biological science and supported biodiversity conservation and reforestation programs in West Sumatra.